2021
DOI: 10.1007/s10552-021-01511-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in breast cancer-risk factors between screen-detected and non-screen-detected cases (MCC-Spain study)

Abstract: Purpose The variation in breast cancer (BC)-risk factor associations between screen-detected (SD) and non-screen-detected (NSD) tumors has been poorly studied, despite the interest of this aspect in risk assessment and prevention. This study analyzes the differences in breast cancer-risk factor associations according to detection method and tumor phenotype in Spanish women aged between 50 and 69. Methods We examined 900 BC cases and 896 controls aged betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Sedentary behaviour could increase the bioavailability of free oestrogens, which are known to play an important role in the development of HR+ phenotype BC [ 38 ]. Furthermore, screen-detected BC is influenced by hormonal factors, reflected in the higher diagnosis rate of HR+ tumours [ 39 ]. Therefore, the fact that the cancers included in this study are screen-detected could influence the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedentary behaviour could increase the bioavailability of free oestrogens, which are known to play an important role in the development of HR+ phenotype BC [ 38 ]. Furthermore, screen-detected BC is influenced by hormonal factors, reflected in the higher diagnosis rate of HR+ tumours [ 39 ]. Therefore, the fact that the cancers included in this study are screen-detected could influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that women participating in screening programs tend to have healthier behaviours [ 41 , 42 ]. On the other hand, other studies have shown that BC most frequently diagnosed in screening are HR+ [ 39 ]. These circumstances could influence the characteristics of our sample.…”
Section: Discussionmentioning
confidence: 99%